Heterogeneous Memristive Devices Enabled by Magnetic Tunnel Junction Nanopillars Surrounded by Resistive Silicon Switches. (3rd January 2018) - Zhang, Yu; Lin, Xiaoyang; Adam, Jean‐Paul; Agnus, Guillaume; Kang, Wang; Cai, Wenlong; Coudevylle, Jean‐Rene; Isac, Nathalie; Yang, Jianlei; Yang, Huaiwen; Cao, Kaihua; Cui, Hushan; et al.
Abstract: Emerging nonvolatile memories (NVMs) have currently attracted great interest for their potential applications in advanced low‐power information storage and processing technologies. Conventional NVMs, such as magnetic random access memory and resistive random access memory, suffer from limitations of low tunnel magnetoresistance, low access speed, or finite endurance. NVMs with synergetic advantages are still highly desired for future computer architectures. This study reports a heterogeneous memristive device composed of a magnetic tunnel junction (MTJ) nanopillar surrounded by resistive silicon switches, named resistively enhanced MTJ (Re‐MTJ), which may be utilized for novel memristive memories, enabling new functionalities that are inaccessible for conventional NVMs. The Re‐MTJ device features a high ON/OFF ratio of >1000% and multilevel resistance behavior by combining magnetic switching together with resistive switching mechanisms. The magnetic switching originates from the MTJ, while the resistive switching is induced by a point‐switching filament process that is related to the mobile oxygen ions. Microscopic evidence of silicon aggregated as nanocrystals along the edges of the nanopillars verifies the synergetic mechanism of the heterogeneous memristive device. This device may provide new possibilities for advanced memristive memory and computing architectures, e.g., in‐memory computing and neuromorphics. Abstract : A nanoscale heterogeneous memristive device combining the advantages of magnetic random access memory (MRAM) and resistive random access memory is demonstrated. The device is based on a resistively enhanced MRAM element integrated with an magnetic tunnel junction nanopillar surrounded by silicon filaments that behave as resistive switches. The device features magnetic switching together with a high ON/OFF ratio of >1000% and multilevel resistance behavior.